Ecocinema in Pukapuka: Climate Change and Pacific Island Futures in Gemma Cubero del Barrio’s Our Atoll Speaks (2019) and The Island in Me (2021) - Gemma Blackwood (eTropic: electronic journal of studies in the tropics)
Examining tropical futurisms through cinema, this paper analyzes two recent documentary films directed by Spanish-American filmmaker Gemma Cubero del Barrio: the short film Our Atoll Speaks: Ko Talatal Mai to Matou Wenua (2019) and the feature documentary The Island in Me (2021). Each is filmed on the remote Pacific Island atoll of Pukapuka in the Cook Islands and features Pacific writer Florence “Johnny” Frisbie. The latter of these two films has been promoted by Cubero del Barrio as the first feature film ever made on Pukapuka, and both films in different ways consider the existential threat of climate change—especially sea level rise—on the island’s longevity and future. Ultimately, I argue that Cubero del Barrio’s documentaries successfully convey ideas about local knowledge and ways of preparing for climate-led change through their representations of the natural environment and local customs. By drawing upon the generic elements of ecocinema and environmental documentary, both films operate as environmental communication texts that aim to educate and inform audiences about damaging epistemological belief systems, while suggesting alternative ways of understanding the interrelation between the human, more-than-human, and place: hence providing meaningful ideas for tropical Pacific futurity.